Hepatitis C testing in sexual health services in England, 2002–7: results from sentinel surveillance. Issue 2 (26th October 2009) - Tweed, Emily; Brant, Lisa; Hurrelle, Martin; Klapper, Paul; Ramsay, Mary; ,
Abstract : Objectives: To describe testing for hepatitis C virus (HCV) in sexual health services in England between 2002 and 2007, using data from a sentinel surveillance study of hepatitis testing. Methods: Data on all anti-HCV tests carried out between 2002 and 2007 were collected from 20 participating laboratories. Test requests originating in sexual health services were identified, allowing analysis of the demographic and clinical characteristics of individuals tested in this setting. KC60 statutory returns data were used to estimate the proportion of new genitourinary medicine clinic attendees tested for hepatitis C each year. Results: 90 424 individuals were tested for anti-HCV in 100 sexual health clinics; 3.2% (n=2858) were found to be positive. Multivariable analysis showed anti-HCV status to be associated with male sex and a reported history of injecting drug use. In those clinics for which data on trends were available, testing for anti-HCV increased over the study period and the percentage testing positive decreased. KC60 data suggested that most clinics tested less than 20% of new patients for anti-HCV, although the proportion of patients tested increased over time. Conclusions: Sexual health services have become increasingly important locations for hepatitis C testing in England, although the proportion of patients testing positive is low compared with other settings. We suggest that testing in this setting could be better targeted to those most at risk of infection by thorough investigation of risk factors among service users.